The Human Aspects of Globally Distributed Work Teams in the Indian Information Technology Industry: Effect of Justice Perception on Team Performance (Global Journal of Management and Business Research, 2014)
The evolution and improvisation of globally distributed work teams (GDWT) over the past 20 years has been the key enabler for the stellar growth of the Indian IT industry. Global software outsourcing has created a workforce that operates across geographical boundaries of place and time. The Indian software industry has a competitive advantage which includes availability of qualified and talented manpower at low costs as compared to other developing economies (Budhwar, Luthar, Bhatnagar, 2006a; Budhwar, Varma, Singh,
Keywords: GDWT-globally distributed work teams; parparticipatory action research